PENGALIHFUNGSIAN LAHAN RUANG TERBUKA HIJAU (TAMAN KOTA JALAN GARUDA SAKTI) MENJADI RUMAH SAKIT UMUM DAERAH KOTA PEKANBARU - Kusuma, Angga Herlanda Sastra; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Conversion of green open space (garuda sakti city park) became a regional public hospital of Pekanbaru is a policy taken by the city government to overcome the problem of less than maximal health care to the public. However, if viewed based on society needs, especially people who live around the road of garuda sakti, more need green open space. Because green open space is useful to reduce the aridity that occurs on the road of garuda sakti. Green open space can also be used as a facility for entertainment and refreshing for various circles. Because of the green open space in the form of a park, there is nothing at all in the garuda sakti area.According to law no. 26 of 2007 on spatial planning, confirmed that the ideal composition of green space (green open space) of a city is 30% of the total area. In this research about diversion of green open space (garuda sakti city park) became a regional public hospital of Pekanbaru , then the researcher uses the theoretical concept proposed by prof. Dr. Ir. Sumbangan Baja, M.Phil about the process of land conversion. Baja suggests there are 3 elements in the process of land conversion, that is internal factors, external factors and policy factors. This research uses qualitative research with descriptive study. In data collection, researchers used observation, interview and documentation.The results of this study indicate that the policy of conversion of green open space (garuda sakti street park) to become regional a public hospital of Pekanbaru is an inappropriate policy. Because the society and the environment around the road of garuda sakti more need green open space.Keywords: Land Conversion, Green Open Space